The impact of Chinese textile imperialism on Nigeria's textile industry and trade: 1960–2015. Issue 154 (2nd October 2017) - Muhammad, Murtala; Mukhtar, Mansur Ibrahim; Lola, Gold Kafilah
SUMMARY: This briefing examines the effects of globalisation and the challenge posed by China to the Nigerian textile industry in the twenty-first century. The meteoric rise of imports of cheap Chinese textiles into the Nigerian market, which was formerly dominated by local fabrics, has shifted the balance in favour of the imports, which has consequently destroyed the economic base of the local textile industry.